Paula Coutinho’s outstanding contribution to the definition of Machado-Joseph disease - Garcia, Bruno Carniatto Marques; Germiniani, Francisco Manoel Branco; Marques, Paula; Sequeiros, Jorge; Teive, Hélio Afonso Ghizoni (Arquivos de Neuro-Psiquiatria, 2017)
Machado-Joseph disease, also known as spinocerebellar ataxia type 3, is the most common form of autosomal dominant ataxia in the world. Paula Coutinho, a highly-regarded Portuguese neurologist worldwide, had a seminal participation in the definition of this disease, more than 40 years ago.
Keywords: ataxia; spinocerebellar ataxias; Machado-Joseph disease; neurology; history